ICT in Agricultural Research for development for rural India - V., Himanshu (Indian Farming, 2018)
Agriculture plays a vital role in India’s economy. Over 58% of the rural households depend on agriculture as their principal means of livelihood. Agriculture, despite its declining share in total output (GDP), is largest employer. The NITI Aayog has proposed various reforms in India’s agriculture sector, including liberal contract farming, direct purchase from farmers by private players, direct sale by farmers to consumers, and single trader license, among other measures, in order to achieve the target of doubling rural income in the next five years, a goal set by union budget 2016-17.